Implementation of geocast-enhanced AODV-bis routing protocol in MANET - Ooi, C. C.; Fisal, N. (2004)
Mobile ad hoc network (MANET) represents a complex distributed system that enables seamless internetwork in areas with no pre-existing communications infrastructure. Far less effort has been done on the real-world basis, with intensive evaluations through simulations. This paper outlines our experiences with the implementation of MANET testbed based on geocast-enhanced AODV-bis module. AODV-bis is an improved design of MANET routing protocol, from the lessons learned beyond the experimental RFC AODV effort. The main goal of our research is to develop and verify the practicality of AODV-bis (ad-hoc on-demand distance vector-bis) routing protocol, featuring path accumulation. To enhance AODV-bis, location information is utilized during route discovery to limit forwarding zone by geocasting. It can be done with only little modification of packet format. We found that AODV-bis, compared to AODV, is a more powerful routing protocol especially in disseminating route information. Its overall performance is further improved with the aid of geocasting.